Uma atividade didática envolvendo área e volume do cilindro e de prismas - Bernardini, Geferson (2014)
This paper presents a didactic proposal for Spatial Geometry classes in High School. We were taken to create this proposal from our experience as a teacher, when we observed that the study of this content requires experimentation and contextualization activities. The study of the Spatial Geometry is of great importance in High School. It contributes to the development of the capacity of abstraction, solving practical problems of everyday life and helps to acquire skills to estimate and compare results, recognize properties of geometric shapes, calculate areas, volume and working with different units of measure. Our work uses as motivation the problem of constructing a silo for grain storage, for this it is necessary to compare the volumes of the prisms with triangular, square and hexagonal base and of the cylinder without the cover, height and total area of the fixed surface to choose the format representing the highest volume. Our work is not intended to define or obtain formulas to calculate areas and volumes. The main focus of this work is to develop the ability to manipulate these formulas and other knowledge, such as solving quadratic equation, using the Pythagorean theorem, and correctly use the calculator to solve a practical problem. This activity has been applied to three classes of Second Grade High School students in a State School of São Paulo in Agudos town. For this purpose two classes of 100 minutes were used. The pupils enjoyed the activity that was carried out in groups of three and the lesson was without complications. This is a didactic sequence that does not require many resources and may be useful for teachers who want to work the theme in context. Our proposal adopts suggestions from the National Curricular Parameters (NCP) and we believe that can be used by fellow teachers, to which our product is available.